White matter integrity in delinquent emerging adults and non-delinquent controls, and its relationship with aggression, psychopathic traits, and cannabis use - Jansen, Jochem M.; Zijlmans, Josjan; Popma, Arne; Marhe, Reshmi (Frontiers in Behavioral Neuroscience, 2022)
Background Atypical white matter integrity may be one of the biological factors related to delinquency. In adults, decreased white matter integrity has been related to antisocial behavior, but findings from research in adolescent and young adult populations are either mixed or lacking. Here we investigated this association within a naturalistic sample of delinquent young adults (age 18-27). Methods In a sample of 95 young adult, delinquent men and 22 age and gender matched controls, we assessed white matter integrity through fractional anisotropy and mean diffusivity measures. We compared white matter integrity between the groups, and within the delinquent group assessed the association between white matter integrity and aggression, psychopathic traits, and cannabis use. Results We found no differences in fractional anisotropy or mean diffusivity between delinquent young adults and non-delinquent controls. Additionally, within the group of delinquent young adults, we found no associations between white matter integrity and aggression, psychopathic traits, or cannabis use. Conclusion Our null findings suggest that white matter integrity differences may be unrelated to antisocial behavior in emerging adults, and/or that white matter differences between delinquent populations and controls may only arise later in life.